Impurity distribution in n-ZnSe crystals doped with Au - Nedeoglo, Dumitru (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2005)

(untitled)
Hall effect, electric conductivity and mobility of charge carriers in n-ZnSe single